Pengaruh program multi-exercise terhadap fungsi kognitif pada lansia overweight dan tidak overweight - Tri Mei Khasana; Ari Tri Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
The effect of the multi-exercise program on cognitive function in overweight and non-overweight elderlyBackground: Cognitive function is the factor that determines the disability of the elderly to live a healthy and independent life. The results of studies regarding the protective effect or detrimental effects of overweight or obesity on cognitive function in the elderly are still controversial. Objective: This study aims to determine the effect of the multi-exercise program on cognitive function in the elderly based on nutritional status.Methods: This quasi-experimental study with a pretest-postest design study involved 37 elderly aged 60-74 years. Body mass index (BMI) derived from the measurement of body weight and height were grouped into overweight and not-overweight. Both groups received a multi-exercise in the form of gymnastic exercise (30 minutes), square stepping exercise (30 minutes), and puzzle games (30 minutes). The intervention was given 12 times with a frequency of 3 times per week. Cognitive function was measured by using the Mini-Mental State Examination (MMSE) questionnaire. Data analysis used paired sample t-test and independent t-test. Results: The multi-exercise program intervention given affected improving cognitive function in the overweight elderly group (p=0.003). However, it is different from the non-overweight elderly group who did not show a significant effect of the multi-exercise program on the cognitive function (p=0.184) even though there was an increase in the mean cognitive function at the end of the intervention. Conclusions: Multi-exercise program intervention for 4 weeks with a frequency of three times per week can improve the cognitive function of the elderly, but statistically only significant in the overweight elderly group.